An In Vitro Study on the Shear Bond Strength of Feldspathic Porcelain to Nickel Chromium Alloy and Cobalt Chromium Alloy after Various Surface Treatments - Vignesh Kamath; Mayuri Kamath; Abhinav Bhargava; Thilak Shetty; Shobha J. Rodrigues; Umesh Y. Pai; Sharon Saldanha; M. Mahesh; Puneeth Hegde; Prashant Bajantri; Sandipan Mukherjee; Ann Sales (Hindawi Limited, 2022)
Background. To evaluate and compare the shear bond strength of feldspathic porcelain to four distinctively surface-treated Ni-Cr and Co-Cr alloys and to assess the impact of oxidation-heat treatment on porcelain to base metal alloy bond strength. Methods. 40 specimens each of nickel-chromium alloy and cobalt-chromium alloy were cast. A total of four groups of specimens were created. Group I was surface-treated by sandblasting with 50 μm alumina particles, Group II was surface-treated by sandblasting with 110 μm alumina particles, Group III and Group IV were surface-treated with 250 μm alumina particles. In Group IV, after sandblasting initially with 250 μm alumina particles, the alloys were subjected to oxidation and resandblasting with 250 μm alumina particles. Each of the specimen was coated with opaque and body porcelain and fired to a total thickness of 2 mm porcelain. A universal measuring machine was used to assess shear bond strength at a crosshead speed of 0.5 mm/min. Results. Two-way ANOVA followed by Tukey's post hoc test was used to assess the significant difference within the groups. Unpaired t-test was used for the intergroup comparison of the obtained data. The study showed that the size of the air abrasion particles used for sandblasting significantly influenced the porcelain to metal surface bond strength, with p value <0.001. The bond strength values of the two alloys tested showed no major variations. Result also showed that oxidation influences the metal-ceramic bond strength. Conclusions. The bond strength of the metal-ceramic interface is influenced by the alloy's surface treatment. The oxidation process impacts the bond strength of the metal-ceramic system.